Penile Fracture, Surgical Success and Complications Rate - Sami Ur Rahman, Noorshad Khan, Asif Khan, Mohammad Rashidullah, Sami Ullah, Saifullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of current study is to determine the causes, symptoms of penile fracture and post-operative outcomes. Study Design: Prospective study Place and Duration: Conducted at Urology department of Miangul Abdulhaq Jehanzeb Kidney, Swat for the duration of one year from 1st January to 31st December, 2020. Methods: Total 30 patients had penile fracture were presented in this study. Included cases were aged between 20-50 years. After receiving informed written permission, detailed demographic information about the enrolled patients was compiled, including age, body mass index, place of residence, and marriage status. Causes and clinical features of fracture were assessed. Patients were undergone surgery and success rate was observed. Post-treatment rate of complications among enrolled cases were also calculated. We used SPSS 22.0 version to analyze complete data Results: Included patients had mean age 35.7±12.32 years with mean BMI 24.7±4.31 kg/m2. Majority of the cases were married 26 (86.7%) and rest were unmarried 4 (13.3%). 12 (40%) patients had urban residency and majority were had rural 18 (60%). Most common cause of fracture was coital 20 (66.7%), followed by masturbation in 6 (20%) and 4 (13.3%) patients had manipulation during sleep. Deformity, swelling, detumescence and crackling sound was the most common symptoms. Right corpus was the most common tunical tear 24 (80%) and most common site was proximal 22 (73.3%). Success rate was found among 26 (86.7%) cases. Post-operatively complications were found among 5 (16.7%) cases in which plaques/ nodules, curvature, erectile dysfunction, pain and swelling were included. Conclusion: For the purposes of this study, we found the penis fracture to be a rather simple condition to diagnose. Cavernosography may be used to confirm a diagnosis if necessary. Penile fractures may be successfully treated with immediate primary surgical repair, resulting in normal erection without substantial sequelae. Short hospital stays and fast restoration of sexual function are common outcomes of this procedure.